1994
DOI: 10.1111/j.1440-1754.1994.tb00627.x
|View full text |Cite
|
Sign up to set email alerts
|

Retention and use of personal health records: A population‐based study

Abstract: A parent-held record has been issued to all children born in New South Wales (NSW), Australia since 1988. Five years after its introduction, an evaluation was undertaken to determine its retention rate over time, rate of documentation of immunization status and other important child health information, and its perceived usefulness to parents. The cross-sectional study comprised an interviewer administered questionnaire to 622 households derived from a stratified random sample of 25 local government areas, repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
47
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 8 publications
3
47
1
Order By: Relevance
“…16 These trends mirror research in paper based PHRs, which show high support for PHRs, but relatively low utilization. 25 This suggests that until PHRs provide valuable functions that improve care on some level, or in other ways promote "stickiness," adoption rates will remain low.…”
Section: Phr Adoption and Attitudesmentioning
confidence: 99%
“…16 These trends mirror research in paper based PHRs, which show high support for PHRs, but relatively low utilization. 25 This suggests that until PHRs provide valuable functions that improve care on some level, or in other ways promote "stickiness," adoption rates will remain low.…”
Section: Phr Adoption and Attitudesmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12] This study is, however, the first to examine parents' perceptions of the utility of the developmental checklists in the health booklet as a tool for developmental surveillance and screening in Singapore. Data on how much of the developmental checklists are completed, parents' awareness and use of the developmental checklists, and how user-friendly parents find the health booklet, will be important information to plan further modifications of the health booklet and to develop it as a main tool of developmental surveillance and screening in Singapore.…”
mentioning
confidence: 99%
“…As the PCHR exists in most European countries, this approach could be possible almost everywhere [32]. English, Australian and French studies that have examined use of PCHRs, although they did not specifically assess the validity of the neonatal information they contained, suggested that items on the neonatal period (birth weight, Apgar scores and information related to delivery) were satisfactorily completed and so potentially useful in epidemiological studies [33][34][35][36][37].…”
mentioning
confidence: 99%